Feeling Abandoned and Exiled: Trait Mindfulness as Moderator the Impact of Ostracism on the Work Meaningfulness - Aliyah Salsabila; Endang Parahyanti (Eduvest - Journal of Universal Studies, 2024)
Academics have concluded that work meaningfulness is the basic need of employees that should be pursued. However, challenges arise in creating a perception of work meaningfulness caused by various factors in the workplace. Workplace ostracism is a potential factor that can affect the perception of work meaningfulness, this is because the condition of being isolated or ostracized is often categorized as an interaction that causes pain and harm to the victim. Individual differences, especially trait mindfulness, are thought to have a strong role in the relationship between the two. Researchers gathered 305 employees from various industries to give statements to the survey given online. The results of data analysis using Moderation Analysis model 1 in PROCESS macro show that workplace ostracism is negatively correlated with work meaningfulness (b = -0.5164). The results also showed that trait mindfulness can play a role as a buffer against the negative relationship between workplace ostracism and work meaningfulness (b = 0.1146). In addition, researchers have also found that the trait mindfulness was also able to predict the employees' work meaningfulness (b = -0.2786).